Kepuasan Kerja Terhadap Turnover Intention dengan Psychological Capital Sebagai Mediator pada Karyawan Generasi Z - Indah Sulastri; Lita Ariani; Julaibib (IDEA: Jurnal Psikologi, 2025)
Generation Z has unique characteristics in the world of work, often showing high turnover rates. Job satisfaction is considered one of the main factor influence the decisions to stay or leave a job, while psychological capital can be a mediating variable in the relationship. This study aim to determine the effect of job satisfactions on turnover intention and whether psychological capital is a variable that acts as a mediator in the relationship between the two variable. The approach used in this study is a quantitativ correlational approach. Respondents in the study were 167 Generation Z employees at Hospital X. The data collected were analyzed using simple mediation analysis. The result of the analyz show that psychological capital acted as a mediator in the influence of job satisfactions on turnover intentions in Generation Z employees at Hospital X. Based on these results, Hospital X is expected to be able to organize training programs that focus on increasing job satisfaction, as an effort to strengthen employee psychological capital which will ultimately reduce turnover.